The impact of remote arts on prescription: Changes in mood, attention and loneliness during art workshops as mechanisms for wellbeing change - Nicola J. Holt (Nordic Journal of Arts, Culture and Health, 2023)
Purpose: To assess the impact of art workshops delivered remotely, during the coronavirus pandemic, on the wellbeing of participants. To measure the impact of participating in art workshops on immediate experience (mood, attention and loneliness). To extend understanding of the mechanisms for wellbeing change. Methodology: An observational, pre-post design, where 60 participants completed: (1) measures of global wellbeing and loneliness at the beginning and end of art on prescription programmes; and (2) 690 ‘in-the-moment’ questionnaires assessing mood, loneliness and attentional absorption (‘flow’) at the start and end of each art workshop. Findings: Participants were most commonly referred to help with stress and anxiety and low mental wellbeing. There was a significant increase in global wellbeing and a reduction in loneliness after participation in the programme. After each art workshop there was a significant increase in: hedonic tone (contentment) and energetic arousal (alertness) and a significant decrease in tense arousal (anxiety) and loneliness. Reduction in tense arousal and loneliness, and entering an absorbed attentional state, during art workshops, significantly predicted changes in global wellbeing across the programme. Originality: The findings suggest that arts on prescription can be beneficial for wellbeing when delivered remotely. They suggest multiple mechanisms for wellbeing change: affective (reducing anxiety); cognitive (absorbed attention); and social (reducing loneliness), which has implications for delivery.